2010
DOI: 10.1002/jbm.a.32678
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects of sol‐gel‐derived bioactive glass nanoparticle on aerobic bacteria

Abstract: The aim of this work was to evaluate the antibacterial effect of bioactive glass nanopowders. The 58S, 63S, and 72S compositions were prepared via the sol-gel technique. Characterization techniques such as X-ray diffraction, transmission electron microscopy (TEM), Zetasizer, and X-ray fluorescent were used. The antibacterial activity was studied using Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, and Staphylococcus aureus. Cytotoxicity of the samples was evaluated using mouse fibroblast L929 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 35 publications
5
96
0
Order By: Relevance
“…silver, cerium ions) or alkaline ions leading to local pH rise. [56][57][58] ZnO QDs are effective antibacterial agents, and their antibacterial activity is considered to be from the production of H 2 O 2 from ZnO QDs, the release of Zn ions, or the generation of reactive oxygen species (ROS). 59 The reported minimum inhibition concentration (MIC) of Zn ions against S. aureus was lower than 9 mg mL…”
Section: Discussionmentioning
confidence: 99%
“…silver, cerium ions) or alkaline ions leading to local pH rise. [56][57][58] ZnO QDs are effective antibacterial agents, and their antibacterial activity is considered to be from the production of H 2 O 2 from ZnO QDs, the release of Zn ions, or the generation of reactive oxygen species (ROS). 59 The reported minimum inhibition concentration (MIC) of Zn ions against S. aureus was lower than 9 mg mL…”
Section: Discussionmentioning
confidence: 99%
“…This antibacterial effect may be related to the addition of BG, which may exert this effect by its chemical composition and the dissolution conditions in its surroundings. 11 The released ions (such as Ca, P and Si) can increase the osmotic pressure, creating an environment where the bacteria cannot grow. 23,24 In order to further verify the ions released by the Col/BG nanofibers, inductively coupled plasma emission spectrometry was used to detect the concentration of ions in the BHI; the results showed that the Col/BG nanofibers released a certain amount of Ca, P and Si ions ( Table 2).…”
Section: Antibacterial Activity Of the Col/bg Nanofibersmentioning
confidence: 99%
“…10 BG also has been found to exert an antibacterial effect when challenged with bacteria in some studies. [11][12][13] Therefore, the development of a skin wound dressing with fish collagen and BG seemed to be extremely interesting. It was necessary to study the amount of BG added to fish collagen and the appropriate technology to make the composites achieve the anticipated multifunctional effects, including a certain tensile strength, antibacterial activity and the capability to effectively induce skin regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…BGs are more bioactive than calcium phosphate compounds; in addition, the silicabased BGs bioactivity reactions are faster than hydroxyapatite (HA). One of the most important characteristics of BGs is that they can provide an ideal environment for genetic control and stimulation of human osteoblasts to be proliferated and di erentiated as they lead to bone formation both in vitro and in vivo with rapid bone regeneration [1,14,15]. There are two processing methods for synthesizing BGs: traditional melt quenching and versatile sol-gel methods.…”
Section: Introductionmentioning
confidence: 99%
“…Between them, due to producing small glass particles with a high-surface area, increased resorption rate, and higher bioactivity, the sol-gel method is more attractive than the other [6,16,17]. Some of certain BGs have also shown the antibacterial e ect [1,18]. For instance, particulate Bioglass r is one of the materials which displays signi cant antibacterial e ect on certain oral bacteria [19].…”
Section: Introductionmentioning
confidence: 99%